The Organization of Central American States. A Chapter in the history of Central American Integration. 1950-1991 - Solano Muñoz, Edgar (2020)
The objective of the article is to historically follow up on the Organization of Central American States (ODECA), between 1951-1991. Sources generated by this organization, particularly by the General Secretariat, were used. The article shows that the ODECA has been the most comprehensive integration scheme within the initiatives of the region between 1960 and 1980; the priority of the Central American States for economic integration detracted from validity and life of the ODECA.